The socialization of the anthropologist-consultant: from practice to the normative frameworks of policy - Agudo Sanchíz, Alejandro (Revista de Antropología Social, 2013)
Whether they reject or advocate so-called applied anthropology, many anthropologists share logics similar to those of the members of policy’s professional communities. This overlap is reflected in assumptions about the separation of theory and “its” practice, as well as in different attempts to resolve the tension between the general and the particular. Both these similarities and the epistemological differences between anthropology and policy are outlined here through an account of a development programme’s impact assessment. Even before beginning fieldwork and returning with their ethnographic descriptions to the institutional arenas of policy, anthropologist-consultants are disciplined and socialized into the art of reinterpreting their research results in terms of the programme’s model. Practice produces and orders policy, yet such practice resides precisely in the interpretive efforts by diverse development practitioners to sustain coherent representations of reality against the contingency of events.
Keywords: anthropology and consultancy; public policy; Mexico; development; impact assessment